1996
DOI: 10.1002/pro.5560051007
|View full text |Cite
|
Sign up to set email alerts
|

Surface point mutations that significantly alter the structure and stability of a protein's denatured state

Abstract: Significantly different m values (1.9-2.7 kcal mol-' M") were observed for point mutations at a single, solventexposed site (T53) in a variant of the B1 domain of streptococcal Protein G using guanidine hydrochloride (GuHCI) as a denaturant. This report focuses on elucidating the energetic and structural implications of these m-value differences in two Protein G mutants, containing Ala and Thr at position 53. These two proteins are representative of the high (mi-) and low ( m -) m-value mutants studied. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 46 publications
(50 reference statements)
1
46
1
Order By: Relevance
“…Previous work has shown that introducing nonnative local structural propensity into a protein can lead to a compaction of the unfolded state (35). In addition, a single Ala-to-Thr substitution in the ␤-sheet of a variant B1 domain of protein G caused an increase in folding rate and compaction of the unfolded state, as assessed by the m f3u values derived from folding kinetics experiments (36). A point that argues against a significant alteration in the unfolded-state structures of the Gly-48 mutants is that their m f3u values do not deviate from the WT value.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that introducing nonnative local structural propensity into a protein can lead to a compaction of the unfolded state (35). In addition, a single Ala-to-Thr substitution in the ␤-sheet of a variant B1 domain of protein G caused an increase in folding rate and compaction of the unfolded state, as assessed by the m f3u values derived from folding kinetics experiments (36). A point that argues against a significant alteration in the unfolded-state structures of the Gly-48 mutants is that their m f3u values do not deviate from the WT value.…”
Section: Discussionmentioning
confidence: 99%
“…The values thus calculated may be interpreted [see Smith et al (1996)] as the apparent radius of gyration of the unfolded state (hence the subindex U we have used in eq 12). The results of the calculation (eq 12) for the urea-induced unfolding of HEW lysozyme at pH 2.9 are shown in Figure 8.…”
Section: Experimental Data Reported In This Work Do Not Provide Suppomentioning
confidence: 99%
“…The occurrence of a collapse preceding protein folding was inferred from kinetic experiments (6)(7)(8)(9)(10)(11) and also reported in equilibrium experiments, using small-angle x-ray scattering (SAXS) (12) and single-molecule fluorescence (13,14). However, the thermodynamics of the CG transition have not been characterized yet.…”
mentioning
confidence: 94%